Konflik Kepentingan Ekonomi Politik dalam Perdagangan Daging Ayam: Studi Kasus Antara Indonesia dan Brasil - Felicia Margaret; Angelia Laksana; Yolanda Yuliani; Ivana Cindi Lydia Wuwung; Deisiree Maria; Leony Ghuusbertha; Linsepda Limbong (Sekolah Tinggi Ilmu Hukum (STIH) Prof Gayus Lumbuun, 2025)
The chicken meat import dispute between Brazil and Indonesia serves as a clear example of tensions in international trade, involving procedural differences and protectionist policies. Indonesia, as the world’s second-largest Muslim population, applies strict requirements such as halal labeling and general prohibitions on products that do not meet certain standards. Conversely, Brazil, as a major chicken meat exporter, seeks to reduce trade barriers by opposing procedures such as the positive list and import licensing, which are considered burdensome. This study aims to analyze the procedural conflict in the trade dispute and its impact on the trade relations between the two countries. The research method employed is a literature review using a normative approach, focusing on the analysis of trade regulations, import policies, reports, and related official documents. The findings indicate that Indonesia successfully upheld procedures focusing on consumer protection and food safety, while Brazil won claims related to administrative procedures that were deemed burdensome and non-transparent. Thus, while both countries have legitimate interests, these procedural differences can create barriers to global trade, requiring a diplomatic approach and constructive dialogue to seek a fair solution for both parties. The resolution of this prolonged dispute is expected to provide valuable insights for future international trade policies.